Strong Converse Results for Linking Operators and Convex Functions - Ana-Maria Acu; Margareta Heilmann; Ioan Rasa (Journal of Function Spaces)
We consider a family Bn,ρc of operators which is a link between classical Baskakov operators (for ρ=∞) and their genuine Durrmeyer type modification (for ρ=1). First, we prove that for fixed n,c and a fixed convex function f, Bn,ρcf is decreasing with respect to ρ. We give two proofs, using various probabilistic considerations. Then, we combine this property with some existing direct and strong converse results for classical operators, in order to get such results for the operators Bn,ρc applied to convex functions.